The panorama of scientific productions regarding environmental accounting in the years 2011 to 2021: A bibliometric review - Supptitz, Samuel; Angonese , Rodrigo; Pereira , Andre da Silva (Seven Editora, 2023)
This article aims to map and analyze the configuration of international scientific production on environmental accounting, using the international databases ISI Web of Science (Wos) and Scopus. The methodology of bibliometric literature review was used and following the laws of Bradford, Lotka and Zipf the results that addressed the theme were analyzed. R and Excel software were used to treat the data. According to the results the authors who stand out most internationally are Matias Laine, Collin Dey and Tung Dao Nguyen and most of the authors who publish on the subject are from the United Kingdom and Italy with a total of 24 and 17 publications respectively. The publications on the subject have a significantly positive trend, but in some years observed there was a decrease in the number of publications. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-038